On the number of distinct fuzzy subgroups of dihedral group of order 60 - Abdulhakeem, Olayiwola; Babangida, Isyaku (Penerbit Universiti Kebangsaan Malaysia, 2018)
In this paper, we compute the number of distinct fuzzy subgroups of dihedral group of order 60 with respect to a new equivalence relation existing in literature. Our computation shows that the number of distinct fuzzy subgroups of dihedral group of order 60 is 150.